Potential energy surfaces and nonadiabatic transitions in the asymptotic regions of ICN photodissociation to study the interference effects in the F1 and F2 spin‐rotation levels of the CN products. Issue 2 (3rd December 2018) - Kashimura, Tatsuhiko; Ikezaki, Tomoya; Ohta, Yusuke; Yabushita, Satoshi
Abstract : One of the most spectacular yet unsolved problems for the ICN A ‐band photodissociation is the non‐statistical spin‐rotation F 1 = N + 1/2 and F 2 = N − 1/2 populations for each rotation level N of the CN fragment. The F 1 / F 2 population difference function f ( N ) exhibits strong N and λ dependences with an oscillatory behavior. Such details were found to critically depend on the number of open‐channel product states, namely, whether both I ( 2 P3/2 ) and I ( 2 P1/2 ) are energetically available or not as the dissociation partner. First, in the asymptotic region, the exchange and dipole‐quadrupole inter‐fragment interactions were studied in detail. Then, as the diabatic basis, we took the appropriate symmetry adapted products of the electronic and rotational wavefunctions for the F 1 and F 2 levels at the dissociation limits. We found that the adiabatic Hamiltonian exhibits Rosen–Zener–Demkov type nonadiabatic transitions reflecting the switch between the exchange interaction and the small but finite spin‐rotation interaction within CN at the asymptotic region. This non‐crossing type nonadiabatic transition occurs with the probability 1/2, that is, at the diabatic limit through a sudden switch of the quantization axis for CN spin S from the dissociation axis to the CN rotation axis N . We have derived semiclassical formulae for f ( N ) and the orientation parameters with a two‐state model including the 3A′ and 4A′ electronic states, and with a four‐state model including the 3A′ through 6A′ electronic states. These two kinds of interfering models explain general features of the F 1 and F 2 level populations observed by Zare's group and Hall's group, respectively. © 2018 Wiley Periodicals, Inc. Abstract : Potential surfaces of ICN up to the asymptotic region were investigated, and the dominant inter‐fragment interaction was found to switch from the exchange, dipole‐quadrupole, to spin‐rotation interaction before dissociation. The angular momentum recoupling causes a Rosen–Zener–Demkov type nonadiabatic transition for the interfering F 1 / F 2 populations through a sudden switch of the quantization axis for CN spin S from the dissociation Z axis to the rotation N ( Y ) axis. Semiclassical formulae for f ( N ) and orientation are presented.